Acute Effects of Milk vs. Carbohydrate on Bone Turnover Biomarkers Following Loading Exercise in Young Adult Females - Prowting, Joel L.; Skelly, Lauren E.; Kurgan, Nigel; Fraschetti, Emily C.; Klentrou, Panagiota; Josse, Andrea R. (Frontiers in Nutrition, 2022)
Dairy products and impact exercise have previously been identified to be independently beneficial for bone mineral properties, however, it is unknown how the combination of these two osteogenic interventions may alter acute bone turnover. Using a randomized crossover design, we compared the acute effects of consuming milk vs. an isoenergetic carbohydrate control beverage on bone biomarkers following loading exercise. Thirteen healthy female participants (Age=20.3±2.3y; BMI=21.0±1.1kg/m2) consumed either 550 mL of 0% skim white milk (MILK) or 52.7g of maltodextrin in 550 mL of water (CHO), both 5 min and 1h following completion of a combined plyometric (198 impacts) and resistance exercise (3-4 sets/exercise, 8-12 reps/set, ~75% 1-RM) bout. Venous blood samples were obtained pre-exercise, and 15 min, 75 min, 24h and 48h post-exercise to assess serum concentrations of bone resorption biomarkers, specifically carboxyl-terminal crosslinking telopeptide of type I collagen (CTX), receptor activator nuclear factor kappa-β ligand (RANKL), and sclerostin (SOST), as well as bone formation biomarkers, specifically osteoprotegerin (OPG) and osteocalcin (OC). When absolute biomarker concentrations were examined, there were no interaction or group effects for any biomarker, however, there were main time effects (p<0.05) for RANKL, SOST and OC, which were lower, and the OPG:RANKL ratio, which was higher at 75 min post-exercise compared with baseline in both conditions. In addition to assessing absolute biomarker concentrations at specific timepoints, we also evaluated the relative (% change) cumulative post-exercise response (75min to 48h) using an area under the curve (AUC) analysis. This analysis showed that the relative post-exercise CTX response was significantly lower in the MILK compared to the CHO condition (p=0.03), with no differences observed in the other biomarkers. These results show that while milk does not appear to alter absolute concentrations of bone biomarkers compared to CHO, it may attenuate relative post-exercise bone resorption (i.e., blunt the usual catabolic response to exercise).